Bacterial microbiomes from vertically transmitted fungal inocula of the leaf‐cutting ant Atta texana. Issue 5 (27th June 2016) - Meirelles, Lucas A.; McFrederick, Quinn S.; Rodrigues, Andre; Mantovani, Joana D.; de Melo Rodovalho, Cynara; Ferreira, Henrique; Bacci, Maurício; Mueller, Ulrich G.
Summary: Microbiome surveys provide clues for the functional roles of symbiotic microbial communities and their hosts. In this study, we elucidated bacterial microbiomes associated with the vertically transmitted fungal inocula (pellets) used by foundress queens of the leaf‐cutting ant Atta texana as starter‐cultures for new gardens. As reference microbiomes, we also surveyed bacterial microbiomes of foundress queens, gardens and brood of incipient nests. Pseudomonas, Acinetobacter, Propionibacterium and Corynebacterium were consistently present in high abundance in microbiomes. Some pellet and ant samples contained abundant bacteria from an Entomoplasmatales‐clade, and a separate PCR‐based survey of Entomoplasmatales bacteria in eight attine ant‐genera from Brazil placed these bacteria in a monophyletic clade within the bacterial genus Mesoplasma . The attine ant‐ Mesoplasma association parallels a similar association between a closely related, monophyletic Entomoplasmatales‐clade and army ants. Of thirteen A. texana nests surveyed, three nests with exceptionally high Mesoplasma abundance died, whereas the other nests survived. It is unclear whether Mesoplasma was the primary cause of mortality, or Mesoplasma became abundant in moribund nests for non‐pathogenic reasons. However, the consistent and geographically widespread presence of Mesoplasma suggests an important functional role in the association with attine ants.